NILAI-NILAI PENDIDIKAN ISLAM DALAM KARYA-KARYA KH. R. ASNAWI - Nur Khosiin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2018)
This research is focus direction to study about Islamic education values in the KH. R. Asnawi field trip, wich written in the Jawab Soalipun Mu’taqod, Fsalatan and Syi’iran Nasehat holy books. Researcher is tried to bring interpretation toward KH. R. Asnawi think up with looking method his harmony and determine rationale. In the KH. R. Asnawi psychology contemplation and history it’s turn up initial by KH. R. Asnawi field trip. From this holy book too virified about values relevance with Islamic education goal. Researcher used the type of literature research to study in a dept and intensive manner about meaning which consist from that study with to do research approach according to interpretative-descriptive.